2022
DOI: 10.3389/fphar.2022.950886
|View full text |Cite
|
Sign up to set email alerts
|

The roles of glycolysis in osteosarcoma

Abstract: Metabolic reprogramming is of great significance in the progression of various cancers and is critical for cancer progression, diagnosis, and treatment. Cellular metabolic pathways mainly include glycolysis, fat metabolism, glutamine decomposition, and oxidative phosphorylation. In cancer cells, reprogramming metabolic pathways is used to meet the massive energy requirement for tumorigenesis and development. Metabolisms are also altered in malignant osteosarcoma (OS) cells. Among reprogrammed metabolisms, alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 281 publications
0
21
0
Order By: Relevance
“…The FDG-PET imaging reveals that both ZR2002 and JS84 were able to statistically reduce the total glycolytic activity (TLG parameter, Figure 3 C), and we speculate that the inhibition of the EGFR signaling pathway may have interfered indirectly with the reduction in the glycolytic pathway, decelerating the tumor proliferation. In fact, it has been previously observed that EGF signaling activates the first step in glycolysis with hexokinase 2 (HK2) but impedes the last step with pyruvate kinase muscle isozyme M2 (PKM2) in triple breast cancer cells [ 37 ], and that PKM2 expression is aberrantly high in osteosarcoma tissues [ 38 ]. A direct link between PKM2 expression and EGFR activity was also established in human glioblastoma specimens [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FDG-PET imaging reveals that both ZR2002 and JS84 were able to statistically reduce the total glycolytic activity (TLG parameter, Figure 3 C), and we speculate that the inhibition of the EGFR signaling pathway may have interfered indirectly with the reduction in the glycolytic pathway, decelerating the tumor proliferation. In fact, it has been previously observed that EGF signaling activates the first step in glycolysis with hexokinase 2 (HK2) but impedes the last step with pyruvate kinase muscle isozyme M2 (PKM2) in triple breast cancer cells [ 37 ], and that PKM2 expression is aberrantly high in osteosarcoma tissues [ 38 ]. A direct link between PKM2 expression and EGFR activity was also established in human glioblastoma specimens [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that serine‐threonine kinase receptor‐associated protein was up‐regulated during OS progression, enhancing the metastatic ability of OS cells 74 . Some studies have found that inhibition of serine/threonine protein kinases: glycogen synthase kinase‐3β (GSK‐3β), cyclin G‐associated kinase, Polo‐like kinase 1, glycogen synthase kinase 3β (GSK3β), and Polo‐like kinase 2 reduce the malignant phenotype of OS 9,75–79 . Other studies have found that inhibition of serine/threonine protein phosphatases: serine/threonine protein phosphatase 2A (PP2A) and serine/threonine phosphatase type 5 reduce the viability of OS cells 80–82 …”
Section: Amino Acid Metabolism In Osteosarcomamentioning
confidence: 99%
“…Glutamine metabolism drives cancer growth and progression for DNA damage repair, epigenetic modification and immune regulation 8 . Glutamine fuels the tricarboxylic acid (TCA) cycle and acts as a redox donor during the Warburg effect 9 . Increased fatty acid synthesis in cancer cells facilitates membrane biosynthesis and signaling molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular metabolic pathways mainly include glycolysis, lipid metabolism, glutaminolysis and oxidative phosphorylation [ 5 ]. The metabolism of cancer cells differs from that of normal cells in that they have elevated levels of metabolism and maintain a high proliferation rate that is used to resist some cell death signals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%